The connection between the accumulation of structural defects caused by proton irradiation and the destruction of the near-surface layer of Li4SiO4 – Li2TiO3 ceramics - Inesh E. Kenzhina; Artem L. Kozlovskiy; Aktolkyn Tolenova; Meiram Begentayev; Saulet Askerbekov (Optical Materials: X)
The key problem of using lithium-containing ceramics as materials of breeders for the propagation of tritium in thermonuclear reactors is phase stability, as well as the preservation of strength and thermophysical parameters of ceramics during their operation, which is accompanied by the accumulation of fission products in the near-surface layers, alongside mechanical influences from the outside. Moreover, in contrast to other types of ceramics, the presence of lithium in the composition of the samples under study leads to limitations in the use of classical analysis methods (scanning electron microscopy, energy dispersive analysis or optical spectroscopy) of structural changes caused by the accumulation of radiation damage, which requires the use of more complex methods for the assessment of the defect concentration in the structure, as well as establishing their relationship with the deterioration of strength and thermophysical parameters, playing a key role in determining the stability mechanisms and further exploitation of ceramics for tritium production. In this regard, the aim of the study is to determine the kinetics of changes in the near-surface layer of two-phase Li4SiO4 – Li2TiO3 ceramics associated with the accumulation of structural distortions caused by irradiation, as well as their relationship with strain embrittlement and disorder. During the studies, it was found that the accumulation of implanted hydrogen in the near-surface layer under high-dose irradiation initiates deformation distortion processes, the intensity of which depends on the ratio of components in the ceramics, according to which the optimal compositions of two-phase ceramics are ratios of components from 0.3 to 0.6. Determination of the type of defects in the composition of the damaged layer, as well as their concentration, was carried out using the electron spin resonance (ESP) method. During the studies, it was found that at low irradiation fluences, the dominant role in the accumulation of structural defects is played by vacancy defects associated with E′-centers, the formation of which is associated with structural distortions, while as the fluence grows, the structure is dominated by deformation disordering caused by the accumulation of Ti3+ defects and HC2 centers (SiO4 3-), the concentrations of which have a clear dependence on the phase composition of the ceramics.